Effect of Amino Acids Infusion on Maternal and Perinatal Outcome in 3rd Trimester Idiopathic Oligohydramnios - Madiha Afzal, Uzma Aziz, Asma Yasin, Attka Maryam, Nosheen Khurram, Hina Zubair (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Unexplained 3rd trimester oligohydramnios is associated with adverse pregnancy outcomes if not treated appropriately. We conducted this study to evaluate the role of parenteral amino acids to improve amniotic fluid volume in idiopathic oligohydramnios encountered in the 3rd trimester thus improving perinatal outcomes. Methods: This study was conducted at the department of obstetrics and gynecology, Arif Memorial teaching hospital for a period of two years from January 2020 till December 2021. A total of 60 cases of confirmed idiopathic 3rd trimester oligohydramnios were included in the study. They were infused with intravenous amino acid infusion on alternate days for a week then once weekly till the patient was delivered with weekly serial ultrasound monitoring for the increase in AFI. The maternal outcome was noted in terms of mode of delivery. The fetal outcome was noted in terms of healthy newborns, LBW babies, need for NICU admission, and poor Apgar score. All this relevant information was entered in a predesigned proforma. Data were analyzed in SPSS version 22. Results: The mean age of the participants was 28.5±4.6years. The mean gestational age at presentation was 31.4±2.10weeks. There were 25 (41.6%) primi gravida, 35 (58.3%) were multi gravida. The mean value of AFI before amino acid infusion in the study population was 5.1±1.35. There were 11 cases (18%) of AFI <5cm, 49(81%) cases of AFI between 5.1-8cm at the first visit. While after amino acid infusion, 6 (10%) patients were observed in severe oligohydramnios group while 33 (55%) in borderline oligohydramnios group and 21(35%) patients had AFI improved to normal range i.e. >8cm at the time of delivery. The mean increase in AFI after amino acid infusion in the study population at the time of delivery was 2.30±0.65. Out of 60 patients, 42 (70%) delivered by vaginal route at term, 15 (25%) cases delivered by cesarean section, and 1 patient (2%) delivered by instrumental delivery. All these deliveries were at term. While 2 (3.3%) cases were delivered preterm due to no improvement in AFI which remained <5cm even after amino acid infusion. Conclusion: Parenteral amino acid infusion in unexplained oligohydramnios in the third trimester may result in improved pregnancy outcomes.